A framework for evaluating an integrated BIM ROI based on preventing rework in the construction phase - Lee, Myungdo; Lee, Ung-Kyun (Journal of Civil Engineering and Management, 2020)
Construction firms attempt to estimate building information modeling (BIM) return on investment (ROI) to confirm whether BIM effects are sufficiently positive to satisfy decision-makers. Previous studies have presented the ROI in various ways, but a more definitive answer is required to consider possible various effects. Therefore, this study proposes a framework for an integrated BIM ROI, a simple, easy-to-understand, and practical tool that is established from substantive requirements from experts in the construction field. The framework consists of a three-phase process including a total of 11 steps. These phases are assessment planning, primary BIM ROI based on preventing rework, and integrated BIM ROI. Based on the proposed framework, an actual effect analysis of BIM project was conducted and the suitability of the methodology was discussed. The results of applying the framework showed that the primary ROI based on prevented rework costs was about 167.8% and the integrated BIM ROI to consider the overall effect of applying BIM was about 476.72%. In addition, the expert’s discussion confirmed that the framework can be employed as a practical means to evaluate BIM performance. This framework can be provided as a guideline to present an integrated BIM effect and assist to efficiently BIM application.